2020
DOI: 10.1029/2020wr027070
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Fluid Retention Due to Natural Vegetation in a Forest Floodplain Analogue Using the Aggregated Dead Zone (ADZ) Dilution Approach

Abstract: Fluid retention and flow resistance due to natural vegetation remain poorly understood despite the importance of understanding these for flow routing and floodplain revegetation projects. Experiments were undertaken in a shallow earthen channel containing a natural cover of small trees, herbaceous plants, and leaf litter, which were sequentially removed and subjected to a range of flows. A dilution monitoring approach within the Aggregated Dead Zone framework was applied to a series of floodplain vegetated flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…The low-coverage patches resulted in a maximum of three times larger impact on reach-scale dispersion than homogeneous vegetation on floodplains, which can increase D x of compound channels by 1.5-fold (Perucca et al, 2009). In addition, the highest dispersive fractions of our patchy vegetation were larger than reported for randomly distributed woody stems at notably lower flow velocities (D f = 0.2-0.5; Carling et al, 2020).…”
Section: The Influence Of Plant Patches On Dispersion Differs From No...mentioning
confidence: 63%
See 1 more Smart Citation
“…The low-coverage patches resulted in a maximum of three times larger impact on reach-scale dispersion than homogeneous vegetation on floodplains, which can increase D x of compound channels by 1.5-fold (Perucca et al, 2009). In addition, the highest dispersive fractions of our patchy vegetation were larger than reported for randomly distributed woody stems at notably lower flow velocities (D f = 0.2-0.5; Carling et al, 2020).…”
Section: The Influence Of Plant Patches On Dispersion Differs From No...mentioning
confidence: 63%
“…We acknowledge that our data covers a limited range of conditions but expect that the results can be extended to slightly outside the studied ranges of flow velocity, plant density and coverage. The study setting lacking grassy understory likely under‐estimates D x for the commonly observed case with grasses growing below the foliage zone of woody shrubs (Berends et al, 2020; Carling et al, 2020). It would be beneficial to complement the dataset with mean velocities <0.3 m/s typical for lowland channels and floodplains with more pronounced transient storage, and with rarely investigated patch coverages of ~20%–50%.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also suggested that vegetation growth on floodplains is a function of flood magnitude, frequency, and duration (Carling et al., 2020; Chai et al., 2020; Turner, 1974). Williams and Wolman (1984) regarded the regulation of high flows as the only dam‐related factor that was almost certain to encourage vegetation growth.…”
Section: Discussionmentioning
confidence: 94%
“…As vegetated areas increase high-flow water levels (stages at a given large discharge), the characterization of resistance differences between channels and floodplains, and the resulting impact on water levels, is crucial for flood control. Previous studies have also suggested that vegetation growth on floodplains is a function of flood magnitude, frequency, and duration (Carling et al, 2020;Chai et al, 2020;Turner, 1974). Williams and Wolman (1984) regarded the regulation of high flows as the only dam-related factor that was almost certain to encourage vegetation growth.…”
Section: Effects Of Vegetationmentioning
confidence: 99%
“…Understorey shrubs, herbs and grasses are also a source of flow resistance, and experiments suggest that large undergrowth relative to the primary storey can have a substantial influence on vegetation roughness (Berends et al, 2020). The influence of undergrowth will depend on its cross‐sectional area relative to the primary storey and the flow depth (Carling et al, 2020). In the sheoak forest studied here, the undergrowth grasses and sedges, for which the resistance was simulated with a uniform Manning's n of 0.045, were highly flexible and were short compared to the flood depths and tree heights.…”
Section: Discussionmentioning
confidence: 99%